Pembelajaran Bahasa Arab Pada Anak: Perspektif Teori Pembelajaran Kognitivistik Jean Piaget - Rusydi, Muhammad; Musgamy, Awaliah (IAIN Bone, 2023)
Arabic Learning in children is a pedagogical process that directs children in the early days of their growth in perceiving Arabic as a language of communication, both spoken and written. In addressing this process, Jean Piaget has provided a theoretical framework on how an Arabic learning process can take place actively by referring to the activation of cognitive processes that exist in children, which in this case are built on several forms, namely, a) assimilation as a process of changing the Arabic learning environment to fit the existing scheme in children, b) accommodation as a process of changing the existing schema in children to suit the Arabic learning environment, c) equilibrium as a process of achieving children who can handle new information in Arabic learning through the process of assimilation and accomodation, d) disequilibrium as a process where there is an imbalance in children's cognitive processes which in turn becomes a challenge for them in accelerating cognitive development in Arabic learning, e) and organization as a process of unifying various schemes by children into a system of Arabic learningÂ that is coherent with each other. Jean Piaget's cognitivistic learning theory can be one of the theoretical basics and practical frameworks for educators in Arabic learning in children who have their own characteristics compared to adolescents or adults, especially in their respective cognitive structures.